2021
DOI: 10.1148/radiol.2021210231
|View full text |Cite
|
Sign up to set email alerts
|

Relative Enhancement Ratio of Portal Venous Phase to Unenhanced CT in the Diagnosis of Lipid-poor Adrenal Adenomas

Abstract: Background:The development of an accurate, practical, noninvasive, and widely available diagnostic approach to characterize lipidpoor adrenal lesions (greater than 10 HU at unenhanced CT) remains an ongoing demand.Purpose: To investigate whether combined assessment of unenhanced and portal venous phase CT allows for the differentiation of lipid-poor adrenal adenomas from nonadenomas. Materials and Methods:Patients with lipid-poor adrenal lesions who underwent unenhanced and portal venous phase CT with a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Although adenomas have been reported to show rapid wash in the portal vein phase ( 13 , 27 ), they often showed no statistically significant difference in univariate analysis. A recent study ( 12 ) indicated that the ratio of portal venous phase attenuation to unenhanced attenuation allowed sufficient identification of lipid-poor adenomas and nonadenomas. Therefore, we attempted to incorporate the portal vein phase attenuation into the combined model, which was an independent risk factor in multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although adenomas have been reported to show rapid wash in the portal vein phase ( 13 , 27 ), they often showed no statistically significant difference in univariate analysis. A recent study ( 12 ) indicated that the ratio of portal venous phase attenuation to unenhanced attenuation allowed sufficient identification of lipid-poor adenomas and nonadenomas. Therefore, we attempted to incorporate the portal vein phase attenuation into the combined model, which was an independent risk factor in multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the delayed phase and additional radiation exposure may limit the utility of the washout CT protocol ( 12 ). However, the relative percentage wash-in ratio of adrenal lesions from the unenhanced to the portal venous phase can remedy the above defects ( 12 , 13 ). To our knowledge, only a few studies including a large number of lipid-rich adenomas have simultaneously assessed unenhanced attenuation and contrast wash-in features on CT ( 12 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The detection rate of adrenal incidentalomas gradually increases with the application of cross-sectional imaging, accounting for approximately 4-10% of all abdominal computed tomography (CT) examinations (1)(2)(3)(4). Adrenal incidentalomas include solid tumors, such as adrenal adenoma, adrenal pheochromocytoma, adrenocortical carcinoma, and adrenal metastasis, of which adrenal adenoma accounts for 70-80% (4,5).…”
Section: Introductionmentioning
confidence: 99%